2020
DOI: 10.3390/polym12112732
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Temperature Self-Blowing Tannin-Humins Biofoams

Abstract: Ambient temperature self-blowing tannin–furanic foams have been prepared by substituting a great part—even a majority—of furfuryl alcohol with humins, a polyfuranic material derived from the acid treatment at high temperature of fructose. Closed-cell foams were prepared at room temperature and curing, while interconnected-cell foams were prepared at 80 °C and curing, this being due to the more vigorous evaporation of the solvent. These foams appear to present similar characteristics as other tannin–furanic foa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Furthermore the signals of furanic rings C2 and C5 linked by a methylene bridge should appear at 155 ppm indicating that furanic resins of some type have formed as well. Furfural, hydroxyl methyl furfural and other furanic materials are well known to be generated from wood carbohydrates [ 38 , 39 , 40 , 41 , 42 , 43 ], here quite likely being catalyzed from the acetic acid generated by the heat treatment induced hydrolysis of the acetyl groups on hemicelluloses [ 44 ], this being a well-known and studied reaction. The high temperatures between 200–300 °C used for the heat treatment, where other techniques have already shown reactions to occur ( Figure 15 ), indicates that formation of furfural in the heat-treated wood may well occur and that this polymerizes to structures of the type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore the signals of furanic rings C2 and C5 linked by a methylene bridge should appear at 155 ppm indicating that furanic resins of some type have formed as well. Furfural, hydroxyl methyl furfural and other furanic materials are well known to be generated from wood carbohydrates [ 38 , 39 , 40 , 41 , 42 , 43 ], here quite likely being catalyzed from the acetic acid generated by the heat treatment induced hydrolysis of the acetyl groups on hemicelluloses [ 44 ], this being a well-known and studied reaction. The high temperatures between 200–300 °C used for the heat treatment, where other techniques have already shown reactions to occur ( Figure 15 ), indicates that formation of furfural in the heat-treated wood may well occur and that this polymerizes to structures of the type.…”
Section: Resultsmentioning
confidence: 99%
“…A number of peaks fulfilling this requirement are indeed present although the most likely candidate peak is slightly more marked as it is likely to be a superposition of the furan C2 with another signal. The carboxylates band at 173 ppm decreases in heat-treated wood, indicating the heat induced hydrolysis of the acetyl groups on the hemicelluloses [ 43 ], the acetic acid so formed renders sufficiently acid the environment to catalyze the formation of furanic moieties [ 38 , 39 , 40 , 41 , 42 , 43 ]. In all cases, all this indicates is an increase in cross-linking of the system either due to rearrangement of the lignin with itself or of the lignin with other wood constituents, namely, furanic resins generated from the carbohydrates, thus an increase in the water repellence of the heat-treated wood.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, systems where the phase transition of a physical blowing agent is initiated by the exotherm of the polymerization reaction. [95][96][97] To our viewpoint, they are just example of exogeneous physical foaming. Self-foaming polymers can be classified into two main classes depending on their production mode as illustrated in Figure 2 and discussed below: (i) Self-foaming polymers by thermolysis (Figure 2A,B) They concern polymers or precursors of polymers bearing thermolabile groups.…”
Section: Self-foaming Polymers: Definition and Classificationmentioning
confidence: 99%
“…This is already the case for so-called non-furanic humins (composed of humic and fulvic substances in soil) that can be processed with tannins to prepare non-isiocyanate wood adhesives [ 18 ]. Recent examples have demonstrated that furanic humins can be employed in substantial amounts to prepare durable wood panels [ 19 ], biobased composites [ 20 ], or foams [ 21 , 22 ] or as a UV shielding agent for thin PVA films [ 23 ]. It should be noted that humins can be considered reactive thermoset resins pending appropriate activation upon heating [ 24 ].…”
Section: Introductionmentioning
confidence: 99%